Enhancing Academic Writing Through Local Indigenous Digital Textbooks: A Language Education Initiative Aligned with Sustainable Development Goals (SDGs) - Ermawati, E.; Suwandi, Sarwiji; Suhita, Raheni (Universitas Negeri Makassar, 2025)
This study aimed to examine the effectiveness of digital textbooks incorporating local indigenous content in enhancing academic writing skills among students in Indonesian Language Education. Employing a quasi-experimental method with a non-equivalent control group design, the research involved pretests and posttests with 71 participants from two institutions. The findings revealed a statistically significant improvement in the experimental group using indigenous-based digital books compared to the control group. This improvement occurred because the materials integrated local values, enabling students to write contextually by linking cultural relevance to their academic tasks. While overall performance increased, the aspect of sentence accuracy showed no significant gain, indicating areas for improvement. These results highlight the potential of culturally contextualized digital materials to support Sustainable Development Goals (SDGs) by promoting inclusive, quality education through localized pedagogy. Further refinement of digital textbooks is recommended, particularly to enhance linguistic accuracy and broaden language competencies in higher education contexts.